Photobiomodulation and estrogen stabilize mitochondrial membrane potential in angiotensin–II challenged porcine aortic smooth muscle cells. Issue 1 (21st September 2020) - Gavish, Lilach; Gilon, Dan; Beeri, Ronen; Zuckerman, Ayelet; Nachman, Dean; Gertz, S. David
Abstract: Rupture of Abdominal aortic aneurysm (AAA) is among the 15 leading causes of death after age 65. Using high frequency ultrasound, we showed that photobiomodulation (PBM) prevents formation and progression of AAA in the angiotensin‐II (Ang‐II)‐infused, apolipoprotein‐e‐deficient mouse model. In the current study we report that while challenge of porcine aortic Smooth Muscle Cells (SMCs) with Ang‐II (1 μM) resulted in a marked decay in mitochondrial membrane potential (MitMP) vs non‐challenged cells, treatment with PBM (continuous diode laser, 780 nm, 6.7 mW/cm 2, 5 minutes, 2 J/cm 2 ) or pre‐incubation with estrogen (50 nM, 1 hour) significantly attenuated this deterioration in MitMP. We also report that PBM and estrogen markedly affected porcine aortic SMC contraction and modified mitochondrial dispersion reflecting important influence on SMC function. These studies provide strong evidence of the important underlying role of mitochondria in the preventive effect of PBM on formation and progression of AAA and its reduced incidence and delayed onset in women. Abstract : Abdominal aortic aneurysm (AAA) occurs in up to 8% of males over age 65. Approximately 50% of untreated individuals with AAA will die from a rupture. Current treatments are limited to urgent, risky, surgical or endovascular intervention emphasizing the importance of identifying mechanism‐based strategies. This study points to stabilization of mitochondrial function as a major underlying mechanism by which photobiomodulation can prevent progression of AAA and its catastrophic consequences.